Mixed problem with boundary integral conditions for a certain parabolic equation. (1996) - Bouziani, Abdelfatah
Abstract : The present article is devoted to a proof of the existence and uniqueness of a solution of a mixed problem with boundary integral conditions for a certain parabolic equation. The proof is based on an energy inequality and on the fact that the range of the operator generated by the problem is dense.